Cardiorenal disease connection during post-menopause: The protective role of estrogen in uremic toxins induced microvascular dysfunction. (1st July 2017) - Pei, Jiayi; Harakalova, Magdalena; den Ruijter, Hester; Pasterkamp, Gerard; Duncker, Dirk J.; Verhaar, Marianne C.; Asselbergs, Folkert W.; Cheng, Caroline
Abstract: Female gender, post-menopause, chronic kidney disease (CKD) and (CKD linked) microvascular disease are important risk factors for developing heart failure with preserved ejection fraction (HFpEF). Enhancing our understanding of the interrelation between these risk factors could greatly benefit the identification of new drug targets for future therapy. This review discusses the evidence for the protective role of estradiol (E2 ) in CKD-associated microvascular disease and related HFpEF. Elevated circulating levels of uremic toxins (UTs) during CKD may act in synergy with hormonal changes during post-menopause and could lead to coronary microvascular endothelial dysfunction in HFpEF. To elucidate the molecular mechanism involved, published transcriptome datasets of indoxyl sulfate (IS), high inorganic phosphate (HP) or E2 treated human derived endothelial cells from the NCBI Gene Expression Omnibus database were analyzed. In total, 36 genes overlapped in both IS- and HP-activated gene sets, 188 genes were increased by UTs (HP and/or IS) and decreased by E2, and 572 genes were decreased by UTs and increased by E2 . Based on a comprehensive in silico analysis and literature studies of collected gene sets, we conclude that CKD-accumulated UTs could negatively impact renal and cardiac endothelial homeostasis by triggering extensive inflammatory responses and initiating dysregulation of angiogenesis. E2 may protect (myo)endothelium by inhibiting UTs-induced inflammation and ameliorating UTs-related uremic bleeding and thrombotic diathesis via restored coagulation capacity and hemostasis in injured vessels. Highlights: Uremic toxins induce inflammation and disrupt angiogenesis in (micro)vasculature. Estrogen could protect uremic toxins injured microvessels and restore hemostasis. Postmenopausal women with renal disease are prone to microvascular dysfunction.